Sex-specific, inverted rhythms of breeding-site attendance in an Arctic seabird - Huffeldt, Nicholas Per (Biol Lett, 2016)
In contrast to daily rhythms that are common in the presence of the geophysical light–dark cycle, organisms at polar latitudes exhibit many diel activity patterns during natural periods of continuous solar light or darkness (polar day and night, respectively), from 24 h rhythms to arrhythmicity. In Arctic Greenland (73.7° N, 56.6° W) during polar day, we observed breeding-site attendance rhythms of thick-billed murres (Uria lomvia; n = 21 pairs), a charadriiform seabird, which provide biparental care at the colony. We found that U. lomvia egg-incubation and chick-brooding attendance is rhythmic and synchronized to the geophysical day (mean period length [rhythm duration] ± 95% confidence interval = 24.13 ± 0.52 h). Individual pair members had temporally segregated, sex-specific colony-attendance rhythms that were opposite (inverted) to each other, and these sex-specific rhythms were prominent at the population level. Our results provide a basis for investigating circadian systems at polar latitudes and sex-specific parental-care strategies.